Low-nitrogen optimization and numerical simulation of natural gas burners - CHU Heng; WANG Denghui*; WU Feng; HUANG Yuping (能源环境保护)
In recent years, a variety of natural gas low-nitrogen combustion technologies have emerged, but the control effect of a single low-nitrogen technology is always limited. In order to achieve clean combustion and low-nitrogen emissions for natural gas, a new type of low-nitrogen burner has been designed, integrating low-nitrogen technologies such as stratified combustion, swirl combustion, and flue gas recirculation techniques. The aim is to reduce the generation and emission of nitrogen oxides (NO_x) during the combustion process. A burner model with a power output of 14 MW was established, and numerical simulations were conducted to analyze the temperature field, velocity field, and nitrogen oxide (NO) concentration field near the burner outlet under different burner structures and operating parameters. The study investigated the influence of factors such as the swirl intensity of the mixed gas and the outlet velocity of the secondary air on the low-nitrogen combustion performance, in order to optimize the burner′s structure and operating parameters for the best low-nitrogen performance. The results showed that prior to optimization, the burner could distribute the gas uniformly in the outlet cross-section and mix it sufficiently with air. The NO mass concentration in the outlet cross-section was lower than the low-nitrogen emission standard of 30 mg·m^-3. After optimizing the number of gas branches to 8, the concentration of the high-temperature zone and the emission of NO_x were at the lowest level, with an NO mass concentration of 7.61 mg·m^-3 in the outlet cross-section. Optimizing the swirl intensity S_0 of the primary air and the mixed gas to 0.6 reduced the NO mass concentration in the outlet cross-section to as low as 5.04 mg·m^-3. Increasing S_0 enhanced the swirl effect and the internal flue gas circulation within the furnace chamber. Optimizing the outlet velocity of the secondary air to a range of 15-30 m·s^-1 resulted in a "mountain"-shaped NO_x distribution characteristic, effectively reducing NO_x emissions, and achieving an average NO mass concentration of 4.91 mg·m^-3 in the furnace′s outlet cross-section. The optimized new low-nitrogen burner can lead to near-zero NO emissions, providing an important reference for subsequent experiments and engineering practices.